2020
DOI: 10.1155/2020/8880100
|View full text |Cite
|
Sign up to set email alerts
|

Jejunal Intussusception in Adolescent Crohn’s Disease: An Extremely Rare Complication

Abstract: Proximal small bowel intussusception occurring in an adolescent Crohn’s disease patient is an extremely rare entity. It is usually primary without a lead point and quite often a transient phenomenon. We report such transient and intermittent jejunal intussusception in a 16-year-old male, developing immediately in a postoperative period after a stoma reversal for jejunal stricture perforation peritonitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…This surgery can be scheduled according to certain criteria [ 10 ] or in emergencies [ 11 ] and sometimes it is indicative of this disease as was the case with our patient. The discovery of a sequel Crohn was reported in the form of rare case reports of ileo-ileal intussusception in the literature [ 12 ] and in the form of a sporadic case of intussusception on a fibrinoid polyp revealing this disease as presented in our case. The management of intussusception in adults is subject to several recommendations [ 13 , 14 ] and should take into consideration secondary etiologies such as tuberculosis [ 15 ], lipoma [ 16 ], cancer [ 17 ], and rarely Crohn's disease [ 12 ].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This surgery can be scheduled according to certain criteria [ 10 ] or in emergencies [ 11 ] and sometimes it is indicative of this disease as was the case with our patient. The discovery of a sequel Crohn was reported in the form of rare case reports of ileo-ileal intussusception in the literature [ 12 ] and in the form of a sporadic case of intussusception on a fibrinoid polyp revealing this disease as presented in our case. The management of intussusception in adults is subject to several recommendations [ 13 , 14 ] and should take into consideration secondary etiologies such as tuberculosis [ 15 ], lipoma [ 16 ], cancer [ 17 ], and rarely Crohn's disease [ 12 ].…”
Section: Discussionmentioning
confidence: 68%
“…The discovery of a sequel Crohn was reported in the form of rare case reports of ileo-ileal intussusception in the literature [ 12 ] and in the form of a sporadic case of intussusception on a fibrinoid polyp revealing this disease as presented in our case. The management of intussusception in adults is subject to several recommendations [ 13 , 14 ] and should take into consideration secondary etiologies such as tuberculosis [ 15 ], lipoma [ 16 ], cancer [ 17 ], and rarely Crohn's disease [ 12 ]. Consequently, the file was discussed in multidisciplinary staff, and the decision to explore the patient under laparoscopy was retained as recommended.…”
Section: Discussionmentioning
confidence: 68%
“…Intussusception in patients with CD is very uncommon and therefore represents a challenging clinical scenario [ 6 , 12 ]. Due to the rarity of this complication and the potentially fatal consequences we performed a comprehensive review of the existing literature and identified 16 reported cases of adult intussusception (minimum age of 16) associated with CD worldwide from 1979 to the present day [ 9 ], [ 10 ], [ 11 ], [ 12 ], [ 13 ], [ 14 , 17 ], [ 18 ], [ 19 ], [ 20 ], [ 21 ], [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature symptoms ranged from light intermittent abdominal pain over a longer period of time to acute severe crampy abdominal pain, vomiting and intestinal bleeding [ 9 ], [ 10 ], [ 11 ], [ 12 ], [ 13 ], [ 14 , 19 ], [ 20 ], [ 21 ], [ 22 ]. In eleven of the cases, intussusception developed postoperatively in patients with CD who had undergone surgery for complications related to the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation